2004
DOI: 10.1097/01.aids.0000131329.51633.a3
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef is preferentially recognized by CD8 T cells in primary HIV-1 infection despite a relatively high degree of genetic diversity

Abstract: These data show that despite relatively high sequence variability, viral regions within the clade B consensus sequence of Nef are preferentially recognized during primary HIV-1 infection. Later diversification of responses to other proteins during prolonged antigen exposure provides evidence of the initial preferential immunogenicity of Nef epitopes compared to similarly conserved regions within other viral proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
86
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 33 publications
13
86
1
Order By: Relevance
“…2A and B). This observation has also been reported previously for subtype B and other subtypes (22,26,28,35,43,45). However, in this study, clade-specific differences in targeted Nef domains were observed.…”
Section: Study Subjectssupporting
confidence: 92%
See 2 more Smart Citations
“…2A and B). This observation has also been reported previously for subtype B and other subtypes (22,26,28,35,43,45). However, in this study, clade-specific differences in targeted Nef domains were observed.…”
Section: Study Subjectssupporting
confidence: 92%
“…Previous studies have determined that during primary HIV infection Nef-specific CD8 T-cell responses represented a significant ratio (46% to 94%) of the total magnitude of the HIV-specific T-cell response (43). In our B/BF cohort, we characterized the Nef-specific T-cell response by employing a peptide matrix-based IFN-␥ ELISPOT assay followed by confirmation of individual peptide response in a further ELISPOT assay.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The envelope protein is able to evade nAb responses by accumulating multiple amino acid changes, especially in the hypervariable regions, while maintaining full functionality for viral cell entry. CTL responses, however, target epitopes in other viral genes (such as gag and nef) more strongly and/or more frequently, particularly during the initial stages of HIV infection [8][9][10]. Although HIV infection often results in the evolution of viral variants that escape CTL responses [11], recent evidence from transmission pair studies and in vitro growth rate studies suggests that some escape mutations might occur at the expense of viral fitness [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Selection to use the CXCR4 coreceptor plays a part in generating diversity in HIV-1 env; however, CXCR4 usage evolves late into infection, is not observed in all individuals (13,24,25), and involves a small number of residues within env (26)(27)(28)(29). Evolution of escape to cellular immune responses may also play a role in driving the rapid divergence of env, although cellular responses may be stronger and͞or more common to other genes such as gag, nef, and tat, especially during recent HIV infection (30)(31)(32). In contrast, selection by neutralizing antibody responses has been shown to result in rapid, continuous in vivo evolution of viral escape at the phenotypic level (33)(34)(35)(36), and therefore may contribute to the rapid evolution of HIV-1 envelope.…”
mentioning
confidence: 99%